2017
DOI: 10.1016/j.epidem.2017.01.005
|View full text |Cite
|
Sign up to set email alerts
|

Forecasting the new case detection rate of leprosy in four states of Brazil: A comparison of modelling approaches

Abstract: Background: Brazil has the second highest annual number of new leprosy cases. The aim of this study is to formally compare predictions of future new case detection rate (NCDR) trends and the annual probability of NCDR falling below 10/100,000 of four different modelling approaches in four states of Brazil: Rio Grande do Norte, Amazonas, Ceará, Tocantins. Methods: A linear mixed model, a back-calculation approach, a deterministic compartmental model and an individual-based model were used. All models were fit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 29 publications
1
18
0
Order By: Relevance
“…Blok et al showed that, given current control, the NCDR is predicted to remain far above the target of 10 per 100000 by 2020 in several states or districts in India, Brazil, and Indonesia [ 18 ]. By way of validation, similar results were shown in the model comparison article focusing on 4 states in Brazil [ 17 ]. Specifically, long-term predictions of the NCDR trend in Brazil indicated that the target of 10 per 100000 is unlikely to be achieved before 2040 in high- and hyperendemic states.…”
Section: Key Findings From Mathematical Modelingsupporting
confidence: 71%
See 1 more Smart Citation
“…Blok et al showed that, given current control, the NCDR is predicted to remain far above the target of 10 per 100000 by 2020 in several states or districts in India, Brazil, and Indonesia [ 18 ]. By way of validation, similar results were shown in the model comparison article focusing on 4 states in Brazil [ 17 ]. Specifically, long-term predictions of the NCDR trend in Brazil indicated that the target of 10 per 100000 is unlikely to be achieved before 2040 in high- and hyperendemic states.…”
Section: Key Findings From Mathematical Modelingsupporting
confidence: 71%
“…To validate the results of the different models, we have compared the consistency of predictions generated by the respective models [ 17 ]. The range of model frameworks employed covers the gamut of quantitative methodologies: multilevel statistical trend models, statistical back-calculation, compartmental transmission models, and fully individualized simulations.…”
Section: Mathematical Modeling Of Leprosymentioning
confidence: 99%
“…Unfortunately, expert opinion can also suffer from well-known cognitive biases [ 38 ] or from real or perceived economic or political interests. Statistical or mathematical methods for forecasting leprosy [ 39 ] may, within limits, provide greater openness and transparency, helping us understand what data and what structural features determine the value of a forecast. We anticipate that an ensemble-based forecasting algorithm that combines each method may yield better performance than each individual forecasting method (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…However, in comparison with other infectious diseases, we still have limited epidemiological data on NTDs; thus, although we have performed formal model comparisons [10][11][12][13][14][15][16][17][18][19], there remain large uncertainties in processes and parameters that could have an impact on the dynamics, as highlighted below. This means that we need to be cautious about overstating our results, even when the policy need is acute.…”
Section: Quantitative Analysis and Transmission Modeling In Public-hementioning
confidence: 99%
“…The authors of this issue are aiming to increase the repeatability of our science. The code for the models used in this special issue were previously published alongside more technical articles [10][11][12][13][14][15][16][17][18][19] as supplementary information or on our website (www.ntdmodelling.org). The release of raw code is not a complete answer to accessibility and reproducibility, but it is a step in the right direction [20].…”
Section: Quantitative Analysis and Transmission Modeling In Public-hementioning
confidence: 99%